Measurement of Gamma Radiation Beam Profile in the Cross Section by Analyzing of Cherenkov Radiation Generated in the Fiber during Multi-Angle Scanning; Charged and Neutral Particles Channeling Phenomena - Stuchebrov S. G. Sergey Gennadevich; Cherepennikov Yu. M. Yuriy Mihaylovich; Krasnykh A. A. Angelina Aleksandrovna; Miloichikova I. A. Irina Alekseevna (2018, 2018)
Title screen